Total Factor Productivity Estimation in Peru: Primal and Dual Approaches - Céspedes, Nikita (2014)
In this paper we estimate total factor productivity (TFP) growth for the Peruvian economy usingthe primal and dual methods for the period 2003-2012. According to the primal method, a procedure that uses the Solow residual as an indicator of productivity, TFP grew at an average annual rate of 1.6%, adjusted for the quality and usage of the factors of production. According to the dual method, a procedure that considers estimations of the marginal productivities of the factors of production, TFP grew at an annual rate of 1.7%.